Analisis Karakteristik Peserta Didik dalam Pembelajaran Pendidikan Agama Islam - Siska Aprilia; Nevianti Dewi Suyanlis Usmiati; Wan Ajijah; Ridwan Idris; Rappe (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2026)
This article aims to analyze the characteristics of students in Islamic Religious Education (PAI) learning and to explain their implications for planning, implementing, and evaluating instruction in schools. This study used a qualitative approach with a systematic literature review design. Data were collected from recent journal articles, scholarly books, and relevant education policy documents, then analyzed through source selection, classification, critical reading, comparison, and thematic synthesis. The findings show that student characteristics in PAI are multidimensional, covering cognitive readiness, affective and emotional conditions, learning motivation, socio-cultural background, spiritual development, and learning profiles. These characteristics strongly influence the selection of objectives, materials, methods, media, classroom interaction, and assessment strategies. The study concludes that effective PAI learning must be based on an accurate analysis of student characteristics so that instruction becomes more contextual, differentiated, inclusive, and meaningful. The practical impact of this study is to provide a conceptual basis for PAI teachers to design diagnostic assessment, adaptive instruction, and character-strengthening learning practices that are responsive to the needs of contemporary students.